Molecular Assessment of Kidney Allografts: Are We Closer to a Daily Routine - Trailin, Andriy; Hrubá, Petra; Viklický, Ondřej (Physiological research, 2020)
Kidney allograft pathology assessment has been traditionally based on clinical and histological criteria. Despite improvements in Banff histological classification, the diagnostics in particular cases is problematic reflecting a complex pathogenesis of graft injuries. With the advent of molecular techniques, polymerase-chain reaction, oligo- and microarray technologies allowed to study molecular phenotypes of graft injuries, especially acute and chronic rejections. Moreover, development of the molecular microscope diagnostic system (MMDx) to assess kidney graft biopsies, represents the first clinical application of a microarray-based method in transplantation. Whether MMDx may replace conventional pathology is the subject of ongoing research, however this platform is particularly useful in complex histological findings and may help clinicians to guide the therapy.
Keywords: Kidney Transplantation; Transcriptome; Graft Rejection; Allografts; Molecular Diagnostic Techniques; přežívání štěpu; transplantace ledvin; Animals; diagnostické techniky molekulární; Humans; Graft Survival; lidé; alografty; zvířata; rejekce štěpu; transkriptom